(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: In this study we would like to examine the role of risk analysis in the field of intelligence and national security work. Methodology: By reviewing the domestic and international literature, we will be able to list the types and areas of application of risk analysis. Findings: From risk assessment of violence to risk analysis tools specifically used in the fight against terrorism, we are intended to examine based on purely professional judgment, purely statistical and mixed (Structured Professional Judgment) approaches of risk analysis. Value: In our research, we conclude that a so-called structured professional approach seems to be the most rewarding way to assess the risk of potential terrorists, and we see the combination of theoretical and practical knowledge and the inclusion of psychological expertise as the specificities of well-functioning risk assessment tools.